INDEPENDENT LEARNING TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS (SDGs) IN THE ERA OF THE COVID-19 DISRUPTION - Fetty Budi Arifani, PhD (Universal Institute of Professional Management, 2021)
Since the Disruption Era Covid-19 has hampered the continuity of education. Education is one of the pillars that supports world sustainable development for the welfare of all levels of the world community in 2030 through the Sustainable Development Goals (SDGs) program, but since the Covid-19 Disruption Era in Indonesia, it has had a significant impact on the achievements of Sustainable Development Programs, especially in challenges to access to education. Schools are closed, distance learning sounds good but in practice there are many problems especially in rural areas due to limited internet access. In order to prevent and resolve the negative impact of the Covid-19 Disruption Era on the achievement of SDGs 4 goals, namely ensuring inclusive and equal quality education, as well as supporting lifelong learning opportunities for all, the Ministry of Education and Culture launched the Independent Learning program which provides freedom and autonomy to educational institutions, and is independent. from bureaucratization, transforming the education system to make Indonesian education more adaptive.